Nutrition as a link between obesity and cardiovascular disease: how can we stop the obesity epidemic? - van Baak, Marleen A. (Thrombosis and Haemostasis, 2013)
Overweight and obesity are associated with excess cardiovascular risk. To reduce cardiovascular risk at the population level, the prevention of overweight and obesity is key. This requires adoption of a healthy lifestyle, including less inactivity and more moderate-to-vigorous physical activity, and a healthy diet. Diet composition may facilitate weight gain prevention and weight loss. Effects of dietary fats, carbohydrates and proteins will be discussed in this context. Current evidence indicates that moderation of the intake of (saturated) fat, a moderate increase in protein content of the diet, a replacement of refined grain/high glucose index (GI) by whole-grain/low GI carbohydrates and limitation of the consumption of calorically-sweetened beverages are likely to facilitate weight control.
Keywords: Nutrition; obesity; prevention